ANALISIS PENDAPATAN DAN KELAYAKAN USAHA PRODUKSI TEH SERAI PADA BUMG DESA CEUNAMPRONG KECAMATAN INDRA JAYA KABUPATEN ACEH JAYA - Mustafa Usman; Taufiq Amru; Agustina Arida; Bagio Bagio (JURNAL EKOMBIS, 2020)
This study aims to determine whether the lemongrass tea production business can provide income to the entrepreneur and to find out whether the lemongrass tea production business is feasible in terms of income. This research was conducted at BUMG, Ceunamprong Village, Indra Jaya District, Aceh Jaya Regency. This research was conducted in July-September 2019. The location selection was based on the existence of producing lemongrass tea. The results showed that the Lemongrass Tea Business in Ceunamprong Village, Indra Jaya District, Aceh Jaya Regency is profitable and feasible in terms of income in terms of production of lemongrass tea at BUMG, Ceunamprong Village, Indra Jaya District, Aceh Jaya Regency.Keywords: Profits, Production, Selling Prices, Production Costs, Receipts and Revenues